Pengaruh Teknik Nafas Dalam dan Posisi Semi Fowler Terhadap Frekuensi Nafas Pada Pasien Asma - Pratama, Wira Agung; Yenni, Yenni; Oktorina, Rola; Wahyuni, Aria (REAL in Nursing Journal, 2024)
Background: Asthma is a disease characterized by narrowing and inflammation of the respiratory tract which results in shortness of breath (difficulty breathing). Data from (WHO, 2020) shows that the prevalence of asthma in 2019 was 262 million people and caused 455,000 deaths worldwide. The aim of the research is to determine the effectiveness of the deep breathing relaxation frequency technique and semi-Fowler position in the Lung Room of RSU Mayjen H.A Talib, Sungai Full City in 2023. Methods: This type of research is analytical descriptive with a quasi-experimental research design with a one group pre test – post test design technique on patients. asthma. The respiratory frequency assessment was carried out 2 (two) times, namely before (pretest) intervention and after (posttest) intervention. The sample taken by purposive sampling was 21 respondents. Results: The results of this research were that there was an influence of deep breathing techniques and the semi-Fowler position on asthma patients at the H.A Talib maijen hospital, Sungai Full City in 2023 with the Wilcoxon test result being a p value of 0.000. Conclusion: The conclusion of this research is that there is effectiveness of deep breathing relaxation techniques and the semi-fowler position on respiratory frequency. The results of this research can be input for nursing interventions so that nurses provide education to patients and families on how to carry out deep breathing techniques and adjust the semi-Fowler position correctly to reduce shortness of breath in asthma patients